Representation of Library Spaceas Pragmatic Space and Ideological Contestation - Endang Fatmawati; Wening Udasmoro; Ratna Noviani (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2017)
This article discusses the representation of library spaceas a space for pragmatic and ideological contestations. The methodology used here was qualitative by observation, interview and documentation. The study found that pragmatically, space in library can be defined by aspects of function of space, requirement for information, availability of WiFi facility, and phys-ical material. Meanwhile, in ideological contestation, library space can be defined by aspects of historical space and paradoxical space.